Work Loyalty and Work Discipline Increase Organizational Citizenship Behavior (OCB) at Universitas Perintis Indonesia - Yolanda Oktarina; Rafnelly Rafki; Nofriadi Nofriadi; Elfiswandi Elfiswandi; Annisa Weriframayeni; Yulasmi Yulasmi (ARRUS Journal of Social Sciences and Humanities, 2024)
Higher education in Indonesia has experienced rapid development in recent decades, with universities that are central to the delivery of higher education playing an important role in producing quality human resources. In the face of this dynamic development, internal factors in academic organizations, such as job satisfaction, job loyalty, and lecturer work discipline, play a key role in maintaining the quality of teaching, research, and community service. Although job satisfaction, job loyalty, and work discipline have been widely studied in the context of organizations, there have not been many studies that examine the relationship between the three with Organizational Citizenship Behavior (OCB) in lecturers in universities in Indonesia. OCB covers voluntary behaviors that are not included in the formal job description, but have a positive contribution to the overall well-being of the organization. This study aims to determine the Effect of Job Satisfaction, Work Loyalty, and Work Discipline on OCB (Organizational Citizenship Behavior) on Lecturers of Universitas Perintis Indonesia. This study used a quantitative approach with survey methods to collect data from respondents. By using multiple linear regression analysis. Through a questionnaire of 108 respondents, the results turned out to be variables of Job Satisfaction, Work Loyalty, and Work Discipline together against OCB (Organizational Citizenship Behavior) of 0.660 or 66%. It can be concluded that there is a positive and significant influence of Job Satisfaction on OCB (Organizational Citizenship Behavior). The findings of this study can provide practical recommendations to improve job satisfaction, job loyalty, and work discipline, as well as motivate OCB among Universitas Perintis Indonesia lecturers.